Transferable plasmid-mediated drug resistance among non-O1 Vibrio cholerae and rough strains of Vibrio cholerae from Tamilnadu, India. - Sundaram, S. (Cambridge University Press, 1984)
A total of 289 non-O1 Vibrio cholerae (NVC) strains and 20 rough V. cholerae (RVC) strains isolated in an endemic area were tested for antibiotic resistance and for transferable R-plasmids. Twenty three per cent of NVC and 40% of the RVC isolates were found to be resistant to one or more drugs. Eight NVC and four RVC strains possessed multiple drug resistance, varying from four to eight drugs. The common spectrum found in NVC isolates were chloramphenicol and streptomycin (CS) or chloramphenicol, streptomycin, tetracycline and ampicillin (CSTA). Resistance to sulphamethoxazole (Su) and to trimethoprim (Tm) was encountered infrequently. In RVC isolates in addition CSTASuTm determinants, resistance markers to aminoglycosides kanamycin, gentamicin and neomycin were also found. Eighteen of the 27 V. cholerae strains with two or more resistance determinants transferred them en bloc to Escherichia coli K12. The level of resistance in the recipient strain was equal to or greater than that of the donor vibrio strains. Most of the strains possessing solitary resistance markers were unable to transfer them. beta-lactamase production could be demonstrated in 92.8% of the ampicillin resistant strains. None of the strains was resistant to nalidixic acid or furazolidone. The results emphasize the importance of antimicrobic susceptibility determination of V. cholerae isolates, regardless of the serotypes, before commencing chemotherapy.